Analysis Of Differences In Patients' Hemodynamic Status With Pre And Post Suction Hyperoxygenation Measures In Pneumonia Patients On Ventilators - Dwi Santoso; Nurul Hidayah (Poltekkes Kemenkes Semarang, 2026)
Pneumonia remains a major health problem in developing countries. Pneumonia can be fatal if not promptly diagnosed and treated appropriately. If a pneumonia patient experiences a worsening or declines in condition resulting in respiratory failure, the patient will require intensive care. Management of patients with respiratory failure is to use a ventilator. One procedure that can be performed on patients on a ventilator to reduce the buildup of secretions is suction (suctioning out mucus). Suctioning can also trigger several complications, so hemodynamic monitoring is necessary. This study used quantitative research with consecutive sampling data collection techniques. The sample was determined by sample calculation, which in this study was conducted in June-July 2025 for 5 patients and 71 observations. The data collection tools used in this study were patient hemodynamic status observation sheets and a Dräger Vista 120 bed site monitor. The data collection method in this study was carried out using primary data obtained directly by observing the patient's hemodynamic status. This study used descriptive statistics and a paired sample t-test. The pre-post suction hemodynamic status was as follows: blood pressure difference t = 0.977, MAP difference t = 0.598, heart rate difference 0.061, respiratory rate difference t = 0.198, body temperature difference t = 0.505, and oxygen saturation difference t = 0.828. There was no difference in hemodynamic status between pre and post suction action in pneumonia patients on ventilators, because the p value was > 0.05.